Investigating the Benefits of BIM for Mid-Rise Timber Buildings in Canada: A Qualitative Study - Shibani, Dr Abdussalam; Anjli Bhavsar; Dyaa Hassan; Messaoud Saidani; Araz agha (IJRDO - Journal of Mechanical And Civil Engineering, 2021)
Timber has recently gained global popularity as a material for taller building typologies. It is a material much less intensive in resource and energy use and accounts for far less greenhouse gas emissions over its life cycle in comparison to steel and concrete; the two most dominating materials in the Canadian construction industry. Mass-timber is an engineered product, which requires the use of prefabrication and CNC machining. Although this process creates much safer working environments and significantly improves the quality of the delivered products, theoretically allowing mass-timber buildings to go even higher, it requires a high level of collaboration and automation at the beginning stages of the project. It requires strong building information modelling (BIM) which is also a relatively new technological process in the industry. Several tall mass-timber projects have recently been constructed however; there has been limited documentation of the strategies and processes needed for a successful project, ultimately hinging the up-take of this typology. This study takes on a qualitative research approach to unfold the processes, techniques, successes and challenges experienced by industry professionals working with BIM in the context of timber construction. Analysis of the responses shows that there are many benefits associated with BIM, which are also present in the context of timber construction. At the same time however, industry professionals noted that more research, education for both the workforce and clientele, and a stronger push from regulatory boards should be addressed in order for the industry to boom in all of the benefits and success factors that BIM has to offer. Based on the results of this study, it can be concluded that acknowledging these ‘lessons learned’ and implementing the noted strategies more rigorously could be very advantageous for tall-timber construction in the Canadian construction industry.